Severity and Associated Factors of Alarm Fatigue Among Intensive Care Unit Nurses: A Systematic Review and Meta‐Analysis - Ling Zhu; Siying Wei; Yawen An; Wenjun Hu; Xiaofeng Xie (Nursing in Critical Care, 2026)
ABSTRACT Background Alarm fatigue is a critical concern in intensive care units (ICUs), affecting nurse well‐being and patient safety. It may reflect interacting conditions within the clinical work system, yet evidence on its severity and associated factors among ICU nurses remains fragmented. Aim To synthesise evidence on alarm fatigue severity and associated factors among ICU nurses. Study Design Eleven databases were searched from inception to July 2025. Observational studies assessing alarm fatigue among ICU nurses using measurement tools with reported reliability were included. A random‐effects meta‐analysis was performed for alarm fatigue severity, stratified by instrument; associated factors and adverse outcomes were synthesised narratively using direction‐of‐association plots. Results A total of 28 studies involving 6908 ICU nurses were included, of which 27 reported alarm fatigue scores. For the Iranian Alarm Fatigue Questionnaire, the most common instrument, the pooled mean was 26.12 (95% CI: 23.94–28.30). Heterogeneity was extremely high ( I 2 ≈98%) and was not meaningfully explained by subgroup analyses or meta‐regression. Directional evidence suggested that higher alarm fatigue was associated with a greater tendency towards medical errors and higher levels of burnout. Evidence on associated factors was mostly inconsistent or non‐significant, with studies focusing mainly on person‐ and organisation‐level factors. Poorer health, secondary traumatic stress, false alarms and lower trust in alarms tended to show adverse directional signals, whereas job satisfaction, resilience, alarm management support and a better nursing work environment showed potentially protective signals. Conclusions Alarm fatigue among ICU nurses appeared to show a moderate tendency overall, although findings should be interpreted cautiously because of substantial heterogeneity. Evidence on associated factors remains scattered, with task‐, technology‐ and environment‐related factors comparatively underexplored. Relevance to Clinical Practice Alarm fatigue may be usefully considered from a clinical work‐system perspective. Greater attention to task, technology and environmental factors may inform future practice improvement. Review Registration Prospero registration number: CRD42024565806.